Analityka i metafizyka w teorii estetycznej Johanna Gottfrieda Herdera - Michalski, Rafał Andrzej (Humaniora. Czasopismo Internetowe, 2023)
The main purpose of this article is to discuss the basic assumptions of the analytic method in Johann Gottfried Herder’s philosophy of art and theory of sense cognition. Analytic method, along with phenomenology and historical hermeneutics, is an essential component of his innovative project of philosophical aesthetics, which is based on the assumptions of sensualist metaphysics. The goal of Herder’s phenomenology is to isolate the sensory fields on which the various types of art are founded and to grasp the essential, qualitative features of a work of art. Hermeneutics examines the context of historical and cultural conditions that have determined such and not other forms of artistic expression and the laws that govern it. Meanwhile, the analysis of aesthetic categories serves as an organizing framework for synthesizing the findings obtained through the implementation of other research methods, thus laying the foundation for the theoretical edifice of aesthetics. The reconstruction of the analytics and metaphysics of aesthetics will be preceded by a discussion of the philosophical ideas of Leibniz and Baumgarten on which Herder’s theory is based.